2018
DOI: 10.1080/24751839.2018.1537557
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of influence of Thai and Japanese cultures on reasoning in social communication using simulated crowds

Abstract: Difficulties living in unfamiliar cultures are caused by differences in patterns of thinking, points of view, and physical action styles. Learning to understand these different styles is one solution that may help people to live together with their differences. This paper presents our findings on learners' cultural understanding during interaction based on culturally influenced communication in simulated crowds. Japanese and Thai participants were asked to obtain multiple tickets available at two service count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Moreover, cultural influences may also play an essential role in participants' perceptions. A previous study found that Thai people are likely to be collectivist and identify other people as in-group or out-group (Thovuttikul, Ohmoto, & Nishida, 2019). Thus, whenever they feel alone or individuated, they tend to keep quiet, leading to scepticism.…”
Section: Grs Reactionmentioning
confidence: 95%
“…Moreover, cultural influences may also play an essential role in participants' perceptions. A previous study found that Thai people are likely to be collectivist and identify other people as in-group or out-group (Thovuttikul, Ohmoto, & Nishida, 2019). Thus, whenever they feel alone or individuated, they tend to keep quiet, leading to scepticism.…”
Section: Grs Reactionmentioning
confidence: 95%
“…Notwithstanding the well-documented cultural dimensions framework of Hofstede (2001) and cultural layers theory of Trompenaars and Hapden-Turner (1998) Thovuttikul et al, 2018;Nishimura et al, 2009). Hall (1976) argued long ago that national cultures can be categorized by context -the inextricable information surrounding an event and being bound up with the meaning of it -in order to perceive principal cultural differences in communication style or pattern (8 typical ways of communicating or expressing one-self).…”
Section: Culture and Communication Strategiesmentioning
confidence: 99%
“…Notwithstanding the well-documented cultural dimensions framework of Hofstede (2001) and cultural layers theory of Trompenaars and Hampden-Turner (1998) which respectively compare companies based on their orientations and discerning norms and values, research explaining styles of communication have depended on national culture. Most of them differentiate communication styles by using two major cross-cultural communication theories -Hall's (1976) theory of high/low context communication cultures and Lewis' (2005) communication theory (see Thovuttikul et al, 2018;Nishimura et al, 2008). Hall (1976) argued long ago that national cultures can be categorized by contextthe inextricable information surrounding an event and being bound up with the meaning of itin order to perceive principal cultural differences in communication style or pattern (8 typical ways of communicating or expressing one-self).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation